Oculi Sinistra Anterior Uveitis in A 35 Years-Old Man - Ramadhanti, Halika Irza; Nugrahani, Ida (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This case study aims to describe the clinical presentation, diagnosis, and management of a 35-year-old male patient with Oculi Sinistra Anterior Uveitis. It highlights the importance of early intervention in preventing complications, particularly vision impairment. Methodology: The study is based on a case report of a patient presenting with acute unilateral anterior uveitis at the Eye Polyclinic of Karanganyar Hospital. The diagnosis was established through a detailed clinical history, ophthalmologic examination, and symptom analysis. The patient was treated with a combination of topical corticosteroids and antibacterial eye drops, along with oral corticosteroids, to reduce inflammation and prevent infection. Results: The patient presented with symptoms of unilateral eye pain, redness, tearing, and blurred vision. The ophthalmologic examination revealed hyperemic conjunctiva, a cloudy anterior chamber, and a slightly delayed light reflex. Treatment with topical and oral corticosteroids successfully reduced inflammation and improved symptoms. The patient's prognosis was favorable, with expectations of full visual recovery if treatment adherence was maintained. Applications: This case emphasizes the significance of early diagnosis and appropriate treatment of anterior uveitis to prevent severe complications such as glaucoma and cataracts. It also provides insights into the clinical presentation and management strategies that can be applied in similar cases, particularly in regions where epidemiological data on uveitis are limited.